QTL Mapping and Candidate Gene Analysis for Alkali Tolerance in Japonica Rice at the bud Stage Based on Linkage Mapping and Genome-Wide Association Study - Li, Xianwei (Rice (N Y), 2020)
BACKGROUND: Salinity-alkalinity stress is one of the major factors limiting rice production. Damage caused by alkaline salt stress is more severe than that caused by neutral salt stress. Alkali tolerance at the bud stage in rice directly affects seedling survival and final yield when using the direct seeding cultivation model. However, genetic resources (QTLs and genes) for rice breeders to improve alkali tolerance are limited. In this study, we combined linkage mapping and a genome-wide association study (GWAS) to analyze the genetic structure of this trait in japonica rice at the bud stage. RESULTS: A population of 184 recombinant inbred lines (RILs) was utilized to map quantitative trait loci (QTLs) for the root length under control condition (RL), alkaline stress (ARL) and relative root length (RRL) at the bud stage. A major QTL related to alkali tolerance at the rice bud stage, qAT11, was detected on chromosome 11. Interestingly, a GWAS identified a lead SNP (Chr_21,999,659) in qAT11 that was significantly associated with alkaline tolerance. After filtering by linkage disequilibrium (LD), haplotype analysis, quantitative real-time PCR, we obtained three candidate genes (LOC_Os11g37300, LOC_Os11g37320 and LOC_Os11g37390). In addition, we performed phenotype verification on the CRISPR/Cas9 mutant of LOC_Os11g37390. CONCLUSION: Based on these results, LOC_Os11g37300, LOC_Os11g37320 and LOC_Os11g37390 were the candidate genes contributing to alkaline tolerance in japonica rice. This study provides resources for breeding aimed at improving rice responses to alkalinity stress.